An American idea : the making of the national parks - Heacox, Kim (Washington, D.C. : National Geographic Society, 2009)
Looks at the development of the national park in the United States from the 17th century to the formation of the National Park Service in 1916.
Includes bibliographical references (p. 187) and index.
Keywords: National parks and reserves -- United States -- History; National parks and reserves -- United States -- History